Reason, Revelation, and Metaphysics : The Transcendental Analogies - Brown, Montague, 1952- (Book collections on Project MUSE., 2021)
"The author argues that the proper use of analogy opens up reason to revelation. Drawing on ancient and medieval sources (Plato, Aristotle, Plotinus, Aquinas), he discusses the transcendental properties of being (unity, truth, goodness, and beauty) and their analogous application"--